O processo de senhorialização do Sul de Portugal no século XV. O caso do Alentejo - Coelho, André Madruga (2017)
With this project I aim to understand the process by which the south of the Kingdom of Portugal, namely the region known today as Alentejo, witnessed the constitution of areas of seigniorial domain during the Late Middle Ages, especially after the ascension to the throne of the dynasty of Avis, and its meaning for the political culture of late medieval Portuguese monarchy. For this, I seek to know the geographic distribution of these areas; the nature of the jurisdictional powers and rights granted; to identify the receivers of these donations and confirmations made by the king; as well as the relation between the formation and consolidation of these areas and the acquisition of property. At the same time, I intend to analyze the changes in the network and relations between the local powers of the region. Finally, the comparison of the case of Alentejo with other regions of Portugal and the Iberian Peninsula, such as Castile and Aragon, may help to a better understanding of the singularities or parallels of Alentejo relatively to its surrounding regions.